Synergistic effects of creatine supplementation and resistance training in the management of knee osteoarthritis: A narrative review - Muhammad Osama; Bruno Bonnechère; Jean Mapinduzi; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2025)
Knee osteoarthritis (KOA) is a common joint disorder anda leading cause of disability. Although there is no cure,management strategies focus on conservativeapproaches such as pharmacotherapy, nonpharmacologicalsupplementation, physical therapy (PT),and exercise. Pharmacological treatments are widely usedfor pain relief but carry risks of long-term adverse effectsand do not enhance joint or muscle health. Nonpharmacologicalsupplements, including glucosamineand chondroitin-sulphate, are frequently used, althoughtheir effectiveness remains debated. However, PT,particularly resistance training (RT), has shown significantbenefits in improving muscle strength and function inKOA. Creatine supplementation (CS) has recentlyemerged as a promising non-pharmacologicalintervention, particularly when combined with RT. Studiesindicate that while CS alone shows limited benefits inKOA, its combination with RT significantly enhancesmuscle strength, lean mass, physical function, and qualityof life by replenishing phosphocreatine stores, which fuelhigh-intensity muscle contractions during RT.Additionally, CS appears to be safe in short and mid-termuse according to the available studies. Even thoughevidence has shown positive effects of CS without anysignificant adverse effects, very few studies with smallsample sizes have been published in the literatureregarding KOA, reporting varying results. We recommendthat future studies should include larger sample sizes andstandardized measures to strengthen the evidence base. Keywords: Creatine, exercise, physical therapy,physiotherapy, knee osteoarthritis.